Sarthaks Test
0 votes
58 views
in Mathematics by (15.0k points)

Find and correct the errors in the statement: (2a + 3b) (a − b) = 2a2 − 3b2

1 Answer

0 votes
by (24.8k points)
selected by
 
Best answer

L.H.S. = (2a + 3b) (a − b) = 2a × a + 3b × a − 2a × b − 3b × b = 2a2 + 3ab − 2ab − 3b2 = 2a2 + ab − 3b2 ≠ R.H.S.

The correct statement is (2a + 3b) (a − b) = 2a2 + ab − 3b2

Related questions

Welcome to Sarthaks eConnect: A unique platform where students can interact with teachers/experts/students to get solutions to their queries. Students (upto class 10+2) preparing for All Government Exams, CBSE Board Exam, ICSE Board Exam, State Board Exam, JEE (Mains+Advance) and NEET can ask questions from any subject and get quick answers by subject teachers/ experts/mentors/students.

Categories

...